DISKURSUS WANITA MUSLIMAH: Versi Al-Quran dan As-Sunnah - Mulyadi bin Jailani (SYARIAH: Journal of Islamic Law, 2022)
Islam emphasizes that men are protectors of women. Men and women are given by Allah swt advantages and specialties to complement each other. The physical advantages of men and women's reproductive organs should not be understood as advantages or disadvantages, but both must be directed to carry out their functions proportionally. Women in the view of Islam actually occupy a very respectable position. The view of Islam cannot be said to be gender biased. Islam does sometimes talk about women as women (for example in terms of menstruation, pregnancy, childbirth and breastfeeding obligations) and sometimes also speaks as humans without being distinguished from men (for example in terms of the obligations of prayer, zakat, hajj, noble character, amar makruf nahi munkar, eat and drink lawful and so on). Both views aim at directing women individually as noble human beings and collectively, together with men, to become part of a harmonious order (family and society).